The Agency Theory Applied to the Investment Funds - Flávia Zóboli Dalmácio (FUCAPE Business School, 2004)
This article seeks to verify the existence of a relationship between the rate of remuneration charged by the administrators of investment funds and the profitability of these portfolios, under the perspective of the Agency Theory. The Agency Theory seeks to explain the conflicts of interest that can arise from the contractual relationship between a principal and an agent. The agent is the individual who, motivated by his own interests, undertakes to do certain tasks for the principal. This work was developed from a bibliographical review and, based on experimental research, empirical investigations were made, the principal object of which was the test of the hypothesis with relation to cause-effect that could exist between the administration tax and the profitability of the investment funds. However, the results obtained by means of the use of statistical tests did not sustain the hypothesis raised in this work.